Editorial - Mani Man Singh Rajbhandari (Journal of Interdisciplinary Sciences)
Dear Readers, The Journal of Interdisciplinary Sciences (JIS) wishes to announce the publication of its first issue in November 2017 bringing together an assessment of the articles from the interdisciplinary sciences. This issue covers subjects from the disciplines of education, engineering, humanities, and science. It is our pleasure to disseminate the deep well researched knowledge to the readership. The Journal of Interdisciplinary Sciences (JIS) is an academic platform for author(s) and readers where researched knowledge and intelligence can be shared through that is assimilated from various interdisciplinary field of study. It is the journal mission to join and collaborate with authors to strengthen the hidden and scattered knowledge to disseminate widely through as JIS act as the proficient outlet for academic, scientific endeavor that supports and help the author(s) through the scientific peer review from the expert reviewers. The beginning is yet a step forward for the JIS to embark on the life-wide and life-long academic journey. Journal of Interdisciplinary Sciences (JIS) commitment towards consistency in publication is another walk towards the academic journey. It has been a pleasure to share and learn from authors and reviewers from interdisciplinary sciences, which is also the mission of the JIS. The next issue will be published in May 2018. We invite the authors, scientists, scholars, researchers, students, managers, leaders from interdisciplinary sciences to submit their papers. The Journal of Interdisciplinary Sciences (JIS) is thankful to all the editorial team, support team and the expert/advisors for their contributions. Most of all, JIS appreciate and is thankful to all the reviewers for their valuable input and scientific and academic rigor in commenting and suggesting the authors work and for their time spared to review the papers. Let us join and collaborate together to ENRICH the BEAUTIFUL MINDS TOWARDS INTELLIGENT MINDS Mani Man Singh Rajbhandari. Ph.D. Founder and Editor-in-Chief Journal of Interdisciplinary Sciences (JIS)